The influence of book tax differences , cash flow volatility, managerial ownership, amount of accruals and company size on profit persistence (case study of consumer services sub-sector companies listed on the Indonesian Stock Exchange in 2017 - 2021) - Adena, Cindini; Suhendar, Dadang; Syarifudin, Syahrul (Lembaga Penelitian Universitas Swadaya Gunung Jati, 2023)
The purpose of this study was to determine the effect of Book Differences, Cash Flow Volatility, Managerial Ownership, and Amount of Company Size Accruals on Earnings Persistence. The methods used in this research are descriptive and verification. The population in this research is the financial reports of consumer services sub-sector companies listed on the Indonesia Stock Exchange for 2017-2021, namely 40 research companies. The sampling technique in this study used purposive sampling and obtained a sample of 21 companies. Astatistic used is panel data regression, while the hypothesis test uses the f-test and t-test. Based on the simultaneous test results of Book Tax Differences Cash Flow Volatility, Managerial Ownership, Accrual Amounts, and Uk have a simultaneous effect on earnings persistence, and based on the partial test of Tax Differences, Cash Flow Volatility, Managerial Ownership, Al Amounts and Sizes have a positive and significant effect on earnings persistence.